2013
DOI: 10.2478/s11535-013-0160-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of auxins on somatic embryogenesis and alkaloid accumulation in Leucojum aestivum callus

Abstract: In vitro cultures of Leucojum aestivum are considered as an alternative for the production of galanthamine, which is used for the symptomatic treatment of Alzheimer’s disease. We studied the effects of auxins 2,4-dichlorophenoxyacetic acid (2,4-D), 4-amino-3,5,6-trichloropicolinic acid (picloram), 3,6-dichloro-o-anisic acid (dicamba) at concentrations of 25 and 50 µM on the induction of embryogenic callus and its capacity to induce somatic embryogenesis and alkaloid accumulation. The embryogenic response of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 51 publications
1
21
0
1
Order By: Relevance
“…Embryos formed in the presence of phenolic compositions lack sufficient amounts of sucrose to carry out the metabolic activity and thus stop in the globular stage. It should be noted that the inhibitory effect of phenolic compositions due to their high concentration in cells leads to protein deposition, enzyme deactivation, or membrane damage [18, 64]. However, in some studies, it has been reported that phenols usually have a reinforcing effect on somatic embryogenesis, but it is possible that phenols interaction with alcohols and other phytochemical compositions of essential oil inhibits their reinforcing effect on embryogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Embryos formed in the presence of phenolic compositions lack sufficient amounts of sucrose to carry out the metabolic activity and thus stop in the globular stage. It should be noted that the inhibitory effect of phenolic compositions due to their high concentration in cells leads to protein deposition, enzyme deactivation, or membrane damage [18, 64]. However, in some studies, it has been reported that phenols usually have a reinforcing effect on somatic embryogenesis, but it is possible that phenols interaction with alcohols and other phytochemical compositions of essential oil inhibits their reinforcing effect on embryogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…minor (Skrzypek et al, 2007) and Galanthus elwesii (Bach et al, 2004). In contrast, Hrubcová et al (1994), Nieves et al (2003) and Ptak et al (2013) reported that non-embryogenic calli produced more phenolics than embryogenic ones. The study of Ozyigit et al (2007) indicates that the role of the phenolic compounds depends on its chemical structure, plant species, the biological process studied (organogenesis or somatic embryogenesis), and its developmental stage.…”
Section: The Influence Of Growth Regulators On Several Biochemical Pamentioning
confidence: 86%
“…Similar trends were also observed in studies on somatic embryogenesis in the cultures of Saccharum sp. (Garcia et al, 2007), Narcisus (Malik et al, 2009), and Leucojum aestivum (Ptak et al, 2013).…”
Section: Growth Regulators (M)mentioning
confidence: 99%
“…In vitro plants of Leucojum aestivum were regenerated from somatic embryos obtained on a solid Murashige and Skoog (MS) [13] medium supplemented with 5 µM zeatin and 0.5 µM benzyladenine (BA) according to the procedure described by Ptak et al [8,12]. For experiment 28-day-old plants (0.3-0.5 g FW each plant), were transferred to MS medium contained 30 g L -1 sucrose and 10 µM paclobutrazol, or 10 µM ancymidol, or 10 µM GA 3 .…”
Section: Effect Of In Vitro Culture Conditions On the Formation Of Lementioning
confidence: 99%
“…Micropropagation ensures rapid multiplication of selected genotypes, allowing the useful metabolites to be collected in greater quantities. Several studies on Leucojum aestivum multiplication by organogenesis and somatic embryogenesis have been performed [5,8,9]. Species that naturally produce bulbs, like Leucojum aestivum can be induced to form bulbs in in vitro culture.…”
Section: Introductionmentioning
confidence: 99%